2016
DOI: 10.4254/wjh.v8.i1.58
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients with hepatocellular carcinoma for liver transplantation: Past and future

Abstract: The aim of liver transplantation (LT) for hepatocellular carcinoma (HCC) is to ensure a rate of disease-free survival similar to that of patients transplanted due to benign disease. Therefore, we are forced to adopt strict criteria when selecting candidates for LT and prioritizing patients on the waiting list (WL), to have clarified indications for bridging therapy for groups at risk for progression or recurrence, and to establish certain limits for downstaging therapies. Although the Milan criteria (MC) remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 99 publications
0
12
0
4
Order By: Relevance
“…Another meta-analysis (23) of 1,198 patients indicated that the presence of vascular invasion, poor differentiation, tumor diameter over 5 cm, and tumor status beyond the Milan criteria were independent risk factors for HCC recurrence. Unfortunately, these large studies do not include biomarkers such as AFP and DCP, however, there have been numerous reports (21,22,24), as well as the present study that report the significance of these biomarkers in predicting HCC recurrence after LT. Two other major Japanese centers, Kyoto (25) and Kyushu (26), indeed, include DCP value as their expanded criteria for HCC patients. The inclusion of biomarkers to the existing criteria based on the number and the size of tumor will be a critical issue in the future debate regarding the indication of LT for HCC.…”
mentioning
confidence: 76%
“…Another meta-analysis (23) of 1,198 patients indicated that the presence of vascular invasion, poor differentiation, tumor diameter over 5 cm, and tumor status beyond the Milan criteria were independent risk factors for HCC recurrence. Unfortunately, these large studies do not include biomarkers such as AFP and DCP, however, there have been numerous reports (21,22,24), as well as the present study that report the significance of these biomarkers in predicting HCC recurrence after LT. Two other major Japanese centers, Kyoto (25) and Kyushu (26), indeed, include DCP value as their expanded criteria for HCC patients. The inclusion of biomarkers to the existing criteria based on the number and the size of tumor will be a critical issue in the future debate regarding the indication of LT for HCC.…”
mentioning
confidence: 76%
“…Evaluation of response to locoregional treatment, while on the waitlist, should be performed at three-month intervals by radiological evaluation using the mRECIST (Modified Response Evaluation Criteria in Solid Tumors) criteria (176) and biological markers dosage such as AFP (177) .…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Algumas situações clínicas foram consideradas especiais desde o início, pois, mesmo não afetando seriamente a função hepática, podem levar rapidamente ao óbito sem elevar o MELD. Essas condições são: alguns tumores raros, polineuropatia amiloidótica familiar, síndrome hepatopulmonar grave, algumas doenças metabólicas, hemangiomatose ou doença policística, deficiência de alfa-1 antitripsina e, principalmente, hepatocarcinoma 23,27 . Pacientes com essas condições clínicas recebem 20 pontos adicionais ao entrarem na lista de espera, que são, posteriormente, elevados para 24 e 29 pontos após três e seis meses na lista de espera, respectivamente 26 .…”
Section: A Alocação De Fígados Para Transplante Em Adultos No Brasil unclassified